Answer:
See below (I hope this helps!)
Step-by-step explanation:
When dividing exponential terms of the same base, we can simply subtract the exponents, therefore:
![\frac{x^{6} }{x^{8} } = x^{(6-8)} = x^{-2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B6%7D%20%7D%7Bx%5E%7B8%7D%20%7D%20%3D%20x%5E%7B%286-8%29%7D%20%3D%20x%5E%7B-2%7D)
Answer:
--719
Step-by-step explanation:
its closer to 0
Answer:
there that should help
Step-by-step explanation:
Answer:
Any line can be graphed using two points. Select two x x values, and plug them into the equation to find the corresponding y y values. Tap for more steps.
Step-by-step explanation:
Step-by-step explanation:
if 5s=3h
34s=?
we will criss cross and
<u>5sx</u><u>?</u>=<u>3h</u><u>×</u><u>34s</u><u> </u>
<u>5s</u><u> </u> <u>5s</u>
=19.5h